The Relationship of The Implementation of Physical Distancing with The Level of Social Interaction in Children Aged 3-6 Years Old in Bantal Village, Asembagus District, Situbondo Regency - Rahmawati, Ira; Lisabella, Stefanie Hapy (Pediomaternal Nursing Journal, 2022)
Introduction: Social interaction played an important role in a child's daily life. If there was no balance of intelligence or interactive abilities, it would be difficult for children to live in society. During the Covid-19 pandemic, the government issued a physical distancing policy. Children couldn't meet and interact with their environment. The purpose of this study was to determine the relationship between the application of physical distancing and the level of development (social interaction) of children aged 3-6 years in Bantal Village. Method: The research method used is quantitative with a cross-sectional approach design. The study was conducted 93 children with criteria aged 3-6 years who live in Bantal Village, Asembagus District. The exclusion criteria for sick children, have physical limitations and suffer from mental disorders using the purposive sampling technique. Data collection used measuring tools in the form of a questionnaire on the physical distancing and interaction rating scale (IRS) and used the chi-square for the statistical test. Results: The results of the statistical analysis test using the chi-squere value obtained p<É‘ (p=0.001<0.05) so that there is a relationship between the application of physical distancing and the level of development (social interaction) of children aged 3-6 years in Bantal Village, Asembagus District, Situbondo Regency. Conclusions: There was a relationship between the application of physical distancing and the level of development (social interaction) of children aged 3-6 years during the Covid-19 pandemic in Bantal Village.